A responsabilidade dos adolescentes autores de ato infracional no diálogo entre o direito e a psicanálise - Marinho, Raquel de Melo (2009)
This study result from a work with adolescents who commit infractional act and are inserted at social educative system. It is a work out of the responsibility idea, that is understanding, by a lot of people, like a expected effect in the application and performing a social educative measure. For that we get opinions about the subject with the academics of the laws of the childhood and adolescence in the Brazil and with academics of the psychoanalyse, because it refer a subject surround with the Law and the Crime and can contribute with the criminology, precisely about the conception of a human being and the responsibility. Finally we promoted, from some practical experiences with the tennagers, a dialog between law and psichoanalytic, about the differents notions of responsability